Respuesta :

Answer:

[tex](f-g)(x) = 2x^2+ 6x-5[/tex]

Step-by-step explanation:

Given

[tex]f(x) = 3x^2 + 4x - 2[/tex]

[tex]g(x) = x^2 - 2x + 3[/tex]

Required

Find [tex](f-g)(x)[/tex]

In functions:

[tex](f-g)(x) = f(x) - g(x)[/tex]

Substitute values for f(x) and g(x)

[tex](f-g)(x) = 3x^2 + 4x - 2 - (x^2 - 2x + 3)[/tex]

Open bracket

[tex](f-g)(x) = 3x^2 + 4x - 2 - x^2 + 2x - 3[/tex]

Collect Like Terms

[tex](f-g)(x) = 3x^2 - x^2+ 4x + 2x- 2 - 3[/tex]

[tex](f-g)(x) = 2x^2+ 6x-5[/tex]